Positive Solutions to Periodic Boundary Value Problems of Nonlinear Fractional Differential Equations at Resonance - Lei Hu (International Journal of Differential Equations)
By Leggett-Williams norm-type theorem for coincidences due to O’Regan and Zima, we discuss the existence of positive solutions to fractional order with periodic boundary conditions at resonance. At last, an example is presented to demonstrate the main results.